Adoption of QRIS on Sales Intensity by Mediating the Financial Literacy Level of MSMEs in Surakarta City: Adopsi QRIS Terhadap Intensitas Penjualan dengan Mediasi Tingkat Literasi Keuangan UMKM Kota Surakarta - Adhi, Arief Surya (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2023)
Currently, payment systems have evolved into digital-based payment systems. It is known that this system brings various kinds of benefits to its users, both business owners and consumers. However, it is still a matter of debate whether this system is able to increase sales intensity or not, and it is also still a matter of debate in the academic world whether the tendency of business people to adopt this system is based on their level of financial literacy. Therefore, this research was conducted with the aim of analyzing the direct and indirect correlation between the adoption of the QRIS payment system on the sales and repurchasing intensity of MSMEs in the creative economy sector and the level of education as a mediator. The population in the study were MSMEs in Surakarta City, Central Java Province. The sample for this research was 30 MSME supervisors, selected using the accidental-purposive sampling method. This research's quantitative primary data was collected through online and offline questionnaire surveys, then analyzed using the multiple regression method. The research results indicate that QRIS adoption has a direct and indirect relationship to sales intensity with the level of financial literacy as a mediating variable which has a significant positive and negative relationship.